C1 Esterase Inhibitor Reduces BBB Leakage and Apoptosis in the Hypoxic Developing Mouse Brain - Jung, Susan; Topf, Hans Georg; Boie, Gudrun; Trollmann, Regina (Neuromolecular Medicine, 2019)
Inflammatory pathways involved in blood–brain barrier (BBB) vulnerability and hypoxic brain oedema in models of perinatal brain injury seem to provide putative therapeutic targets. To investigate impacts of C1-esterase inhibitor (C1-INH; 7.5–30 IU/kg, i.p.) on functional BBB properties in the hypoxic developing mouse brain (P7; 8% O2 for 6 h), expression of pro-apoptotic genes (BNIP3, DUSP1), inflammatory markers (IL-1ß, TNF-alpha, IL-6, MMP), and tight junction proteins (ZO-1, occludin, claudin-1, -5), and S100b protein concentrations were analysed after a regeneration period of 24 h. Apoptotic cell death was quantified by CC3 immunohistochemistry and TUNEL staining. In addition to increased apoptosis in the parietal cortex, hippocampus, and subventricular zone, hypoxia significantly enhanced the brain-to-plasma albumin ratio, the cerebral S100b protein levels, BNIP3 and DUSP1 mRNA concentrations as well as mRNA expression of pro-inflammatory cytokines (IL-1ß, TNF-alpha). In response to C1-INH, albumin ratio and S100b concentrations were similar to those of controls. However, the mRNA expression of BNIP3 and DUSP1 and pro-inflammatory cytokines as well as the degree of apoptosis were significantly decreased compared to non-treated controls. In addition, occludin mRNA levels were elevated in response to C1-INH (p < 0.01). Here, we demonstrate for the first time that C1-INH significantly decreased hypoxia-induced BBB leakage and apoptosis in the developing mouse brain, indicating its significance as a promising target for neuroprotective therapy.
CRIS-Team Scopus Importer:2019-08-23
Keywords: BNIP3; DUSP1; Hypoxia; Matrix metalloproteinases; Neonatal brain injury; Neuroprotection; Occludin; S100b protein; Tight junctions